2015
DOI: 10.1016/j.jjcc.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypoalbuminemia, frailty, and body mass index on early prognosis in older patients (≥85 years) with ST-elevation myocardial infarction

Abstract: These findings indicate that the serum albumin level, CSHA-CFS score, and BMI, in addition to serum troponin I level, have an impact on the early prognosis of older patients with STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 33 publications
3
59
0
Order By: Relevance
“…Furthermore, our study is the first to reveal higher mortality among AMI with PEM in the United States. These findings are consistent with the result from the KAMIR‐based study mentioned above and other Asian studies that have used hypoalbuminemia, waist‐to‐hip ratio, body mass index, or other computed measures of nutrition as a surrogate for malnutrition among patients with ST‐elevated AMI undergoing PCI. Our results also concur with studies of PEM in other conditions such as heart failure, acute ischemic stroke, sepsis, hip fractures, and PEM among patients hospitalized in a general medical and surgical floor .…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study is the first to reveal higher mortality among AMI with PEM in the United States. These findings are consistent with the result from the KAMIR‐based study mentioned above and other Asian studies that have used hypoalbuminemia, waist‐to‐hip ratio, body mass index, or other computed measures of nutrition as a surrogate for malnutrition among patients with ST‐elevated AMI undergoing PCI. Our results also concur with studies of PEM in other conditions such as heart failure, acute ischemic stroke, sepsis, hip fractures, and PEM among patients hospitalized in a general medical and surgical floor .…”
Section: Discussionsupporting
confidence: 89%
“…Some single nutritional indices such as albumin have been shown to be closely associated with poor outcomes in patients with CHF 7, 8 . Additionally, to evaluate nutritional status, more complex indices, such as the prognostic nutritional index (PNI), have been developed and widely used 913 .…”
Section: Introductionmentioning
confidence: 99%
“…It seems that lower serum albumin levels are increased risk factors for coronary disease, which could, together with traditional risk factors, assist in confirming patients who are at risk of myocardial infarction (MI) 8, 9 . However, one study has shown that hypoalbuminemia was related to adverse events but not to mortality in patients with acute coronary syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of frailty has been of increasing importance of for cardiovascular health because the association of frailty and increased risk of cardiovascular disease has been recently reported (7), and frailty also adds extra prognostic significance to existing risk model (8). Frail older people were at significant higher risk of mortality and morbidity than non-frail older people across various kinds of cardiovascular diseases (9), encompassing stable coronary heart disease(10), acute coronary syndromes (11), heart failure (12), and surgical interventions (13). The importance of frailty for cardiovascular diseases is not only its prognostic impact, but also the benefits of therapeutic interventions for frailty also improve cardiovascular outcomes (14).…”
Section: Introductionmentioning
confidence: 99%